Changes of Serum Homocysteine and Vitamin B12, but Not Folate Are Correlated With Obsessive-Compulsive Disorder: A Systematic Review and Meta-Analysis of Case-Control Studies - Yan, Sirui; Liu, Hailong; Yu, Yaqiong; Han, Nashu; Du, Wenzhi (Frontiers in Psychiatry, 2022)
Background: Obsessive-Compulsive Disorder (OCD) refers to a clinical complex intellectual disability, and OCD patients are reported to show irresistible obsessive thinking and compulsive behavior. Folic acid acts as a member of Water Soluble Vitamins in the human body, sustaining normal daily activities (e.g., exercise, sleep and memory). Homocysteine, a sulfur-containing non-essential amino acid, has been investigated in numerous psychiatric disorders (e.g., OCD). Vitamin B12 is recognized as a type of complex organic compound with cobalt contained. Moreover, vitamin B12, folic acid deficiency and high levels of homocysteine were demonstrated to influence brain functions as well as lead to non-specific psychiatric symptoms. Objectives: This study aimed to evidence the epidemiology of OCD and investigate whether Vitamin B12, folic acid and homocysteine impact the etiology of OCD. Patients and Methods: A systematic search on eight databases (i.e., Pubmed, Embase, Web of Science, the Cochrane Library, CBM, CNKI, WANFANG DATA, China Science and Technology Journal Database) was conducted, and the retrieval time was up to March 2021. The available articles involving the patients of OCD with/without anomaly of Vitamin B12, folic acid and homocysteine were comprehensively reviewed and analyzed. Results: 5 studies involving 309 patients were included in this meta-analysis, including 172 cases in the experimental group and 137 in the control group. The content of Folic Acid in the OCD group was no significant difference from that in the normal group (SMD=-0.089, 95%CI -1.966 to 1.418, p=0.000). And homocysteine was significantly higher (SMD=1.132, 95%CI 0.058 to 2.558, p=0.020). Vitamin B12 was significantly lower (SMD=-0.583, 95%CI -1.503 to 0.337, p=0.001). Limitations: Due to the low quality of the original literature, there is great heterogeneity in the data, and it is hard to explore the source of heterogeneity. Conclusions: The present meta-analysis showed the anomaly of Vitamin B12, folic acid and homocysteine in OCD patients. However, as impacted by the low comprehensive quality of the included literature and the risk of bias, high-quality case-control studies should be further conducted to explore the association between Vitamin B12, folic acid, homocysteine and OCD. Key words:Obsessive-Compulsive Disorder, Folic Acid, Homocysteine, Vitamin B12, Meta-analysis